Pedaling Toward Revelation: My Summer with Flannery O’Connor - Saxton, Ben (Cambridge quarterly of healthcare ethics, 2018)
This section features original work on pathographies—i.e., (auto)biographical accounts of disease, illness, and disability—that provide narrative inquiry relating to the personal, existential, psychological, social, cultural, spiritual, political, and moral meanings of individual experience. Editors are: Nathan Carlin and Therese Jones. For submissions, contact Nathan Carlin at: Nathan.Carlinuth.tmc.edu.